Aquaculture : an introductory text - Stickney, Robert R. (CABI, 2009)
Covers issues associated with sustainable aquaculture development, culture systems, hatchery methods, nutrition and feeding of aquaculture species, reproductive strategies, harvesting, and other topics. This book also covers other forms of aquaculture, such as the production of seaweeds, recreational fish and ornamental species